Testing for urinary tract colonization before high‐dose corticosteroid treatment in acute multiple sclerosis relapses: prospective algorithm validation. Issue 3 (21st July 2012) - Rakusa, M.; Murphy, O.; McIntyre, L.; Porter, B.; Panicker, J.; Fowler, C.; Scott, G.; Chataway, J.
<x xml:space="preserve">Abstract</x> Background and purpose To evaluate a dipstick algorithm for urinary tract colonization, prior to high‐dose corticosteroid treatment in acute relapses of multiple sclerosis (MS). Methods Prospective cohort study of 267 consecutive patients with MS relapses requiring corticosteroid treatment in a hospital‐based, ambulatory, acute MS relapse clinic. A total of 18 participants met the exclusion criteria, leaving 249 for analysis. Main outcome measures were urinary dipstick sensitivity, specificity, positive predictive value, negative predictive value and safety of antibiotic co‐treatment with high‐dose corticosteroids. Results Significant bacteriuria (≥105 colonies ml) rate in this population was 11% (95% CI, 7.1–14.9). Specificity and sensitivity of positive leucocyte esterase or nitrite were 78% and 65%. Negative predictive value of urine dipstick was 96%. No clinical adverse events occurred in the 3% (95% CI, 0.9–5.1) of patients with a false‐negative dipstick. Eighteen per cent of patients were unnecessarily treated with antibiotics for 48 h. Conclusion Urinary dipstick testing allows for rapid and safe management of patients suffering from an acute MS relapse. The algorithm is conservative, and future work is needed to reduce the false‐positive rate.